Bioethanol production from seaweed solid waste biomass of agar processing. Issue 1 (1st May 2022) - Winarni, I; Uju,; Santoso, J; Wibowo, T
Abstract: This paper describes about the potential application of renewable energy sources from biomass (seaweed waste) to replace fossil fuels combustion which produced CO2 emission and heavy metal pollution. The objective of the research is to utilize the seaweed solid waste from agar production industry for bioethanol feedstock. The enzymatic method was carried out for glucose production with the addition 1% of surfactant Tween 20 during the saccharification process of three kinds of substrate concentration (20, 25, 30% dw) and 10 FPU/g substrate for the cellulose concentration and used S. cerevisae as yeast in the fermentation process for bioethanol production. The result showed that the highest reducing sugar value (122.4 mg/mL) and 2.86% for the bioethanol content were from 30% dw treatment of substrate concentration of solid agar waste. Therefore, the waste from agar industry is a potential raw material to be used as biofuel and could reduce the heavy metal problems.